Bahamarama - Morris, Bob 1950- (St. Martin's Minotaur, 2004)
Having served two years in prison for a crime he did not commit, Zack Chasteen hopes to reunite with his girlfriend in the Bahamas, but when his trip turns dangerous, he turns to a police superintendent and a Taino mystic for help.